Branding the Police Institution on the Youth Santri through Traditional Music and Puppets Stories in Central Java Indonesia - Ulani Yunus; Tri Adi Sumbogo; Bhernadetta Pravitta Wahyuningtyas; Mario N. Willyarto; Rubiyanto (Jurnal Spektrum Komunikasi, 2023)
The purpose of this study is to illustrate how branding activities can do by the police institution through traditional music art performances and puppet stories can do on youth santri in Indonesia to coincide with National Santri Day in Indonesia. The research methods carried out are qualitative with data suber, in-depth interviews, direct observations, and literature studies. The results of the study mentioned problems with police imagery and puppet art imagery. Both of these issues actually become artistic creativity that becomes police branding activities and maintains traditional puppet art, which is also almost abandoned by Z Generation in Indonesia even though puppetry is also an ancestral heritage that received recognition from UNESCO. In conclusion, branding about the police through traditional art performances and puppet stories has been able to make the activity as entertainment and at the same time a disheartce in the hearts of youth students who are studied.